2013
DOI: 10.5539/jas.v5n12p100
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Parameters, Phytochemical Composition and Antioxidant Activity of the Algarvian Avocado (Persea americana Mill.)

Abstract: The physical, chemical and nutritional properties of Persea americana fruits variety 'Hass' produced in the Algarve region were studied. Edible and non-edible parts of the fruits (pulp, seeds and peel) were compared considering their possible contribution to improve the sustainability of the food and pharmaceutical industries. The nutritional contents evaluated were moisture, ash, proteins, fat, total soluble solids and acidity. It were also evaluated the contents of bioactive compounds (phenolics, flavonoids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
59
6
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 41 publications
(40 reference statements)
14
59
6
12
Order By: Relevance
“…10, No. 8;20181999, 2002Villa-Rodríguez et al, 2011;Vinha et al, 2013); these previously reported values were mostly higher than those found in the present study. We inferred that the different cultivation conditions of the avocado accessions could have the main effect on the variation of the total lipid levels of the pulps.…”
Section: Morphological Characteristics Analysescontrasting
confidence: 57%
“…10, No. 8;20181999, 2002Villa-Rodríguez et al, 2011;Vinha et al, 2013); these previously reported values were mostly higher than those found in the present study. We inferred that the different cultivation conditions of the avocado accessions could have the main effect on the variation of the total lipid levels of the pulps.…”
Section: Morphological Characteristics Analysescontrasting
confidence: 57%
“…Distilled water was the blank control. Results were expressed as grams of tartaric acid per 100 g of sample, according to the methodology described by Vinha et al (2013). The experiments were carried out in triplicate for each accession.…”
Section: Titratable Acidity Assaymentioning
confidence: 99%
“…Natural antioxidants, in particular flavonoids and other groups of polyphenols, have potential uses in the pharmaceutical and food industries because of their many benefits such as reducing the risk of inflammatory diseases and preventing lipid oxidation (Chen et al, 2014). Avocado fruit contains more phenolic compounds than other kinds of tropical and subtropical fruits (Kosinska et al, 2012;Vinha et al, 2013;Chen et al, 2014). Recent studies have also demonstrated that avocado contains other bioactive compounds that are equally beneficial to human heath, such as vitamins and phytochemicals (vitamin C, vitamin E, carotene, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…that were at least 2 mm larger than those of the seedlings stored for 10 d. In regard to stem length, it was observed that plants grew up to three times longer by increasing the storage time (between 10 and 100 d). Although avocado seeds are recalcitrant and storage conditions affect seedling emergence (Hartmann et al, 2002), storage under high relative humidity and low temperatures allowed the growth and development of seedlings, which was favored by the characteristic active metabolism and high moisture content of this species (Vinha et al, 2013).…”
Section: Electrical Conductivity Testmentioning
confidence: 99%